A novel LC–MS/MS assay for heparan sulfate screening in the cerebrospinal fluid of mucopolysaccharidosis IIIA patients. (February 2016) - Naimy, Hicham; Powell, Kendall D; Moriarity, John R; Wu, Jiang; McCauley, Thomas G; Haslett, Patrick AJ; Barbier, Ann J; Qiu, Yongchang
Aims: Heparan sulfate (HS) accumulates in the central nervous system in mucopolysaccharidosis III type A (MPS IIIA). A validated LC–MS/MS assay was developed to measure HS in human cerebrospinal fluid (CSF).Methods & results: HS was extracted and digested and the resultant disaccharides were derivatized with a novel label, 4-butylaniline, enabling isoform separation and isotope-tagged analog introduction as an internal standard for LC–MS/MS. The assay has a LLOQ for disaccharides of 0.1 μM, ±20% accuracy and ≤20% precision. CSF samples from patients with MPS IIIA showed elevated HS levels (mean 4.9 μM) compared with negative controls (0.37 μM).Conclusion: This assay detected elevated HS levels in the CSF of patients with MPS IIIA and provides a method to assess experimental therapies.